CORRELATION OF RADON ANOMALIES, MAGNETIC FIELD AND FAULTS ON THE TERRITORY OF KYIV - Оrlyuk, M.; Yatsevskyi, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article considers the location of radon anomalies on the territory of Kyiv and its correlation with the magnetic field and faults. Radiation is one of the essential environment ecological factors. Radon and its decay daughter products in indoor air has a dominant role in the total level of radiation contamination. Identification and evaluation of radon areas is an urgent task to study its effects on human health. The authors used magnetic anomalies as indirect method to estimate radon levels in the upper part of the crust and in the air, measurements of radon concentration having point character. Physical and geological justification for such connection is weak magnetization of acid rocks, altered in fault zones and areas of high content of radioactive minerals. The goal of this research is finding indirect link of radon anomalies with magnetic anomalies and faults. The methodology involves data interpretation of radon survey, magnetic field to construct a map of the magnetic field with radon anomalies and faults. The result obtained can be used within the Ukrainian shield (acid or alkaline rocks, zones of jointing and faults should be located in the investigation area) for building predictive models of radon hazard according to magnetic survey.
Keywords: radon; magnetic anomalies; Kyiv; fault; crystal base